Analisis Economies of Scale pada Kemitraan Ayam Broiler di Indonesia - Rianzani, Citra; Kusnadi, Nunung; Pambudy, Rachmat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Broiler chicken farms that have developed successfully in the world, such as Charoen Pokphand in Thailand and its branches in other countries, are large-scale and vertically integrated businesses. So that the farm is able to achieve economies of scale. On the contrary, most broiler chicken farms in Indonesia are run on a small scale. Under government policy, small-scale broiler chicken farms cooperate with large companies in partnerships. This study aims to identify economies of scale in partnered broiler chicken farms in Indonesia. This study used secondary data of 228 partner farmer units from the 2014 Livestock Business Household Survey by the Indonesian Central Statistics Agency. The analysis used two approach methods, namely statistically descriptive and linear regression models. The results showed that the partnered broiler chicken farms experienced economies of scale, where the production cost per unit is significantly cheaper on an increasingly large business scale. This shows that the government needs to collaborate with broiler chicken companies to implement a livestock group-based partnership model for small-scale farmers to be able to achieve economies of scale.